Perubahan Interaksi Sosial Acara Halal bi Halal pada Masa Pandemi Covid-19 di FISHUM UIN Sunan Kalijaga Yogyakarta - Napsiah, Napsiah; Sanityastuti, Marfuah Sri (FIKRAH, 2020)
During the Corana Virus pandemic, social interaction in the implementation of the halal bi halal tradition was carried out online to anticipate the spread of the Corana Virus. This activity is something new for the Muslim archipelago. Because of this, the interaction changes from offline to online. This study aims to determine the changes that occur when implementing the halal bi halal tradition. Qualitative descriptive method with direct interview and observation techniques and strengthened by using secondary data obtained from previous research, websites and books are used to obtain this information. The findings of this study are that online social interaction does not fully facilitate social interaction, because online interactions cannot display expressions of sincerity, relief, and joy, which are the expressions of Nusantara Islam in expressing halal bi halal. This is because the use of technology is limited by space and time in the zoom meeting media. Thus, conveying the message of halal bi halal to strengthen relationships can use technology, but not to display halal bi halal expressions